P143 Mortality in the western australian mining industry (1996-2011). (1st September 2016) - Sodhi-Berry, Nita; Reid, Alison; Fritschi, Lin; Musk, Arthur; Vermeulen, Roel; Klerk, Nicholas de; Peters, Susan
Abstract : Objectives: Miners are exposed to a range of hazards including injury risks and exposure to carcinogens and inorganic fibres and dusts. We aimed to assess miners' mortality from all and specific causes, including accidents/injuries (intentional and unintentional), cancer, cardiovascular disorders (any, ischaemic heart disease and stroke) and respiratory disorders (any and chronic obstructive pulmonary disease), relative to the general population and identify subgroups at risk. Methods: Registry data identified deaths in a cohort of 198, 981 mineworkers (87% male, mean age: 34 ± 11 years) in Western Australia during 1996–2011. Indirectly standardised mortality ratios (SMRs) were calculated and multivariable Poisson models were used to evaluate ever-underground work, employment commencement year and employment tenure as predictors of mortality within miners after adjusting for age, sex, smoking, socioeconomic status and comorbidity. Results: There were 2, 156 miner deaths over 1, 419, 201 person-years. Cancer (n = 682, 31.6%), unintentional accidents/injuries (n = 678, 31.4%) and ischaemic heart disease (n = 303, 14.1%) were the leading causes of deaths. Compared with the general population, the specific and all-cause mortality rates were lower for both female (SMR: 0.71, 95% CI: 0.57–0.85) and male (SMR: 0.70, 95% CI: 0.67–0.73) miners. Within miners, higher all-cause mortality rates were observed for ever-smokers (Mortality Rate Ratio (MRR): 1.83, 95% CI: 1.65–2.03) and those commencing employment before 1996 (MRR: 3.25, 95% CI: 2.82–3.75), than their counterparts. Increasing trends in mortality were associated with higher comorbidity scores (MRR: 2.51, 95% CI: 2.16–2.90), increasing socio-economic disadvantage (MRR: 1.16, 95% CI: 1.12–1.19) and reducing employment tenures (MRR: 1.77, 95% CI: 1.68–1.86). Similar patterns were observed for the specific causes of death. Ever-underground work was associated with higher, but non-significant, risk of unintentional accident/injury (MRR: 1.33, 95% CI: 0.99–1.79), cancer (MRR: 1.20, 95% CI: 0.90–1.60) and all-cause (IRR: 1.10, 95% CI: 0.95–1.28) deaths. Conclusion: The lower overall death risk among miners compared with the general population may be explained by the healthy-worker effect and short follow-up. However, short-tenured miners, especially those with under 2.5-years of employment, had high comorbidity-adjusted mortality rates.